2019
DOI: 10.2486/indhealth.2018-0166
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prevalence of hepatitis B virus infection among health care workers in a referral hospital in Kisantu, Congo DR: a pilot study

Abstract: We aimed to determine hepatitis B virus (HBV) prevalence and risk factors for health care workers (HCWs) to contract HBV infection in a referral hospital in the Democratic Republic of Congo. From October 2015 to August 2016, we recruited 97 HCWs (55 males and 42 females, aged 41.2 ± 10 yr) from Kisantu St. Luke’s Hospital, a Congolese referral hospital located in the province of Kongo Central. Serum samples were assayed for HBV markers using ELISA. A questionnaire was used to record the HCWs’ demographics, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
6
1
1
Order By: Relevance
“…This finding is in line with a past study of DRC healthcare workers that found an association between multiple sexual partners and HBsAg positivity. 17 We did not observe evidence that engagement in transactional sex was associated with HBsAg positivity. Interestingly, we observed lower HBsAg prevalence among male partners of HBsAg-positive mothers compared with HBsAg-negative mothers.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…This finding is in line with a past study of DRC healthcare workers that found an association between multiple sexual partners and HBsAg positivity. 17 We did not observe evidence that engagement in transactional sex was associated with HBsAg positivity. Interestingly, we observed lower HBsAg prevalence among male partners of HBsAg-positive mothers compared with HBsAg-negative mothers.…”
Section: Discussioncontrasting
confidence: 59%
“…National HBV prevalence in the DRC is estimated to be 3.3% by HBV surface antigen (HBsAg) testing, 11 translating to approximately 2.5 million chronic infections in a country where advanced hepatology care is essentially inaccessible. 12 Estimated prevalence is higher among blood donors, 13 women with HIV presenting to urban antenatal care (ANC) settings, 14 pregnant women in rural areas, 15,16 healthcare workers, 17 and survivors of sexual violence. 18 Blood donor screening and the three-dose infant pentavalent vaccine series are the only HBV prevention measures implemented nationally in DRC, but complete infant HBV vaccination coverage is <70%.…”
mentioning
confidence: 99%
“…Additionally, 80% of participants in the studies were either nurses or doctors. Research suggests that other HCWs, such as patient transporters, also have a considerable HBV occupational risk [ 20 , 21 ]. This study, therefore, extended the screening beyond doctors and nurses and provided testing for all cadres of HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, approximately 2 million HCWs are infected with HBV through needle stick and other sharps injuries [ 4 ]. Previous studies in Africa found high HBV infection and exposure rates (roughly 10%) in HCWs in South Africa and Nigeria [ 5 ]. HBV infections in healthcare settings usually result from both needle stick injuries and failure to adhere to universal infection prevention precautions.…”
Section: Introductionmentioning
confidence: 99%